Kinerja Reksa Dana Saham Dengan Menggunakan Metode Sharpe, Trenyor Dan Jensen Pada Periode Januari 2014 Sampai Desember 2015 - Methirana dan Indra Widjaja (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
The purpose of the research is to analyze the types of equity funds in the stock market and analyze the performance of the funds equity method using sharpe, trenyor methods, and methods of jensen. The research method used is the method of data collection and processing of data by calculation in accordance with methods of sharpe, treynor method and methods of jensen. Method of data collection is composed of effective data from the website of the stock exchange. Calculation method consists of a method of sharpe, treynor method, and methods of jensen. The benefits of this comparison can give you an idea about the objective performance of mutual funds in Indonesia as one of the considerations for investors and potential investors in choosing the best mutual fund, and to an investment manager with the research expected to provide knowledge about the Investment Manager on the performance that they do. In addition to knowing the competition industry mutual funds in Indonesia so as to provide a reference for an investment manager as a determinant of investment policy to increase the return on investment and minimize risk. As well as for the community Provide knowledge and information on the performance of mutual funds in Indonesia.